2013
DOI: 10.1007/978-3-642-32034-7_175
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Z-Scheme of Electron Transport in Oxygenic Photosynthesis

Abstract: Abstract:We start with the discussion of the photosynthetic unit, based on the experiments of Arnold (1932a, 1932b), continue with the first two-quantum proposal by Rabinowitch (1945Rabinowitch ( , 1956), Emerson's Red drop (1943) and Emerson Enhancement Effect (1957) and various action spectra made for understanding the roles of the photosynthetic pigments. The experimental work of Kok (1959) and the theoretical model by Hill and Bendall (1960) were followed soon thereafter by the seminal papers of Duysens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In the chloroplast, thylakoid membranes are laterally differentiated into appressed (grana) region and nonappressed (stroma-exposed) region, and multiprotein complexes are distributed nonuniformly between them (Anderson et al 2008;Anderson 2012). A difference between redox potentials of the photosynthetic electron carriers is the driving force for the non-photochemical reactions of the photosynthetic electron transfer chain described by the classic ''Z-scheme'' (Govindjee et al 2012). An electron is transferred from a redox active molecule with more negative redox potential (reductant) to a molecule with more positive redox potential (oxidant).…”
Section: Energy Transduction In the Chloroplastmentioning
confidence: 99%
“…In the chloroplast, thylakoid membranes are laterally differentiated into appressed (grana) region and nonappressed (stroma-exposed) region, and multiprotein complexes are distributed nonuniformly between them (Anderson et al 2008;Anderson 2012). A difference between redox potentials of the photosynthetic electron carriers is the driving force for the non-photochemical reactions of the photosynthetic electron transfer chain described by the classic ''Z-scheme'' (Govindjee et al 2012). An electron is transferred from a redox active molecule with more negative redox potential (reductant) to a molecule with more positive redox potential (oxidant).…”
Section: Energy Transduction In the Chloroplastmentioning
confidence: 99%
“…The Z-scheme shown above already outlined the energetic relationships between the electron transfer events in the light-reactions of photosynthesis that result overall in the reduction of NADP + by H2O [207]. Immediately following photo-excitation of the primary donors, the initial charge-separated states are formed in both photosystems (P680 + /Pheo − and P700 + /A0 − ) producing the trapped energetic electrons that participate in the "downhill" reduction steps and, concurrently, the strong oxidant P680 + [208,209].…”
Section: Photosystem II In Oxygenic Systemsmentioning
confidence: 99%
“…After the accumulation of four oxidizing equivalents in the Mn-containing oxygen evolving complex (i.e., the S4-state is reached), water oxidation takes place and the fully reduced state (S0) of the oxygen evolving complex is recovered. Meanwhile, the electron transfer events downstream of PS II involve the reduction of a soluble ferredoxin that in-turn reduces the flavoprotein ferredoxin-NADP + reductase [207]. Structural similarity of both PS I and II to the reaction centers is maintained in terms of the overall arrangement and number of cofactors present in the electron transfer chain although in both RCs BChls are substituted for Chl a and derivatives.…”
Section: Photosystem II In Oxygenic Systemsmentioning
confidence: 99%
“…It turned out that the Red Drop of photosynthetic efficiency disappeared if a supplementary light beam of shorter wavelengths was provided (see [7]). As a possible explanation, Emerson and his co-workers, Ruth Chalmers and Carl Cederstrand, suggested that "the significance of the supple- 1 The development of the Z-scheme of photosynthesis already was the subject of earlier accounts, e.g., [1], and recently [2] as well as [3]. See also [4], Chapter VI.…”
mentioning
confidence: 99%
“…mentary light may be that it adds excitation of other pigments besides chlorophyll a"; in the green algae, with which they were working, the authors speculated, this pigment might be chlorophyll b. 3 Tragically, Emerson's untimely death on 4 February 1959 in an airplane crash (at age 56) prevented his further research into these issues.…”
mentioning
confidence: 99%